Acupuncture May Decrease the Incidence of Post-stroke Dementia: A Taiwan Nationwide Retrospective Cohort Study - Chu, Shao-Ang; Chen, Te-Yuan; Chen, Po-Yuan; Tzeng, Wei-Jie; Liang, Cheng-Loong; Lu, Kang; Chen, Han-Jung; Wu, Cheng-Chun; Chen, Jian-Han; Tsai, Chin-Chuan; Wang, Hao-Kuang (Frontiers in Neurology, 2021)
BACKGROUND Post-stroke dementia may affect up to one-third of stroke survivors. Acupuncture as a complementary treatment for stroke has been shown to be beneficial for subsequent post-stroke rehabilitation. The purpose of this retrospective cohort study was to investigate the potential effect of acupuncture to protect stroke patients from dementia. METHODS We included 9,547 patients receiving ambulatory or hospital care for stroke and 9.547 non-stroke patients; patients were matched for sex, age, and Charlson Comorbidity Index. Each individual was traced for the subsequent development of dementia. 2449 stroke patients received acupuncture treatment and 7098 residue stroke patients without acupuncture treatment served as control groups. The cohorts were followed-up until the end of 2007: the incidence and adjusted hazard ratios (HRs) with 95% confidence intervals (CIs) of post- stroke dementia in the Cox proportional hazard regression. RESULTS During the 3-year follow-up, 1,403 patients with stroke (14.70%) and 427 patients without stroke (4.47%) developed dementia. The adjusted HRs of development of dementia among stroke patients were 3.64-times (range, 3.27-4.06), and the incidence of dementia was higher in male. Stroke patients receiving acupuncture treatment had a lower probability of dementia than those without acupuncture during the follow-up period. CONCLUSIONS The association between stroke and dementia existed in both sexes, more prominent in male. Patients with stroke receiving acupuncture treatments showed decreased risk of dementia. Care must be taken evaluating these results because this study was limited to lack of information regarding lifestyles, stroke severities, and acupuncture methods that were used in treatments.